Factorial structure, reliability and validity of the workaholism scale (WorkBAT): Spanish version. - Boada-Grau, Joan; Prizmic-Kuzmica, Aldo-Javier; Serrano-Fernández, María-José; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2013)
This study aims to carry out an adaptation into Spanish of Spence and Robbins’ WorkBAT inventory (1992) and to analyse its psychometric properties. With this objective in mind a version adapted into Spanish of two samples, the first consisting of 285 employees (56.5% women and 43.5% men) and the second of 342 employees (52.9% women and 47.1% men). The first sample, after it was subjected to an exploratory factor analysis, yielded two subscales: motivation/commitment and enjoyment at work. Confirmatory factor analysis (ESEM) was then applied to the second sample, replicating the previous results. Both subscales showed good reliability. The scores from the scales were then related to various external correlates and to other scales and displayed good convergent and criterion validity. The findings indicate that the present scale can be used to evaluate workaholism and furthermore that it is fundamentally a psychometrically sound instrument. The WorkBAT can be used in future research studies as a screening tool in combination with other instruments.